THE EDUCATIONAL CONCEPT OF HAJI AGUS SALIM - Alexander Stark; Khairul Hisyam Baharuddin; Ariezal Afzan Hassan; Nazatul Syima Mohd Nasir, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Haji Agus Salim (1884–1954) was a prominent figure in the Indonesian independence movement. After independence, he became a famous diplomat and served as Indonesia’s Minister of Foreign Affairs. Numerous historians concentrated on his career as a politician. Nevertheless, Haji Agus Salim was also intrigued by educational concepts. Throughout his life, he demonstrated his interest in education in several ways: During the Dutch colonial period he decided to teach his children at home. Later, he was an effective instructor for the Jong Islamieten Bond, and he was also a successful visiting lecturer at Cornell University. In addition to his political expertise, he saw the value of transmitting some educational elements. The underlying structuralist approach of this research revealed that Haji Agus Salim was more concerned with the aspects of language teaching and Islamic knowledge. According to him, it was indispensable that the students develop a motivational and interested consciousness, and the teacher should instigate the eagerness to learn.